Information technology for strategic analysis of IT company projects - Grinchenko, Marina; Moskalenko, Volodymir (CEUR Workshop Proceedings, 2023)
The application of strategic analysis methods for solving a strategic problem and determining the IT company's development directions was considered. The scientific publication analysis of strategic analysis methods to determine the development prospects for companies in various industries was carried out. The IT company that produced several software products or implemented projects for the development of several software types (IT projects) was considered. These software products are used to determine the company's development direction. The IT projects' strategic analysis and their prospects analysis to increase the company's competitiveness were carried out. Information technology for the strategic analysis of a company's software products was proposed. It includes the following steps: 1) strengths and weaknesses analysis of software products using the SWOT analysis for each product and company; 2) software products competitiveness analysis and their market prospects using the SWOT analysis results; 3) identification of the company's main risks associated with the further development and sale of each software; 4) identification of factors and forces that affect the IT-project risks and the company's risks; 5) determination of priorities for the company's IT project development in accordance with the analytical hierarchy process As a result, prospective software products were determined to improve the company's competitiveness.
Keywords: information technology; IT projects; software products; a company's competitiveness; SWOT analysis; the analytical hierarchy process